The culture of digital scholarship in academic libraries - Roemer, Robin Chin; Kern, Verletta; Garber-Pearson, Reed; Fakouri, Maryam; Yee, Perry; Stevens, Elliott (Librarian); Bedford, Elizabeth (Librarian); Lytle, Beth; Muilenburg, Jennifer; Vallier, John Bellarmine, 1968-; Weaver, Andrew (Librarian); Wadland, Justin; et al. (ALA Editions, 2019)
"At the heart of digital scholarship are universal questions, lessons, and principles relating both to the mission of higher education and the shared values that make an academic library culture. But while global in aspirations, digital scholarship starts with local culture drawn from the community. Editors Chin Roemer and Kern invite you into their institutional workspace, the University of Washington, gathering voices from a range of positions that speak to the facets of digital scholarship. This mosaic of perspectives reveals the challenges, questions, and personalities that sit at the nexus of academic libraries and digital scholarship culture. By thoroughly exploring a single institution, this unique volume elucidates the many ways in which digital scholarship can express the values, priorities, opportunities, and challenges of the community's intellectual and technical environment."--Publisher's description